Smart public transportation system in the prospective of Bangladesh using android application and RFID technology - Uddin, Mohammed Adnan; Bithil, Asif Faiyaz; Shihab, Abed Al; Hyder, Mashrah Bin (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.